Effect of Chitosan Nanoparticle-Loaded Thymus serpyllum on Hydrogen Peroxide-Induced Bone Marrow Stromal Cell Damage - Salma Baig; Ainnul Hamidah Syahadah Azizan; Hanumantha Rao Balaji Raghavendran; Elango Natarajan; Sangeetha Naveen; Malliga Raman Murali; Hui Yin Nam; Tunku Kamarul (Stem Cells International)
We have determined the protective effects of Thymus serpyllum (TS) extract and nanoparticle-loaded TS on hydrogen peroxide-induced cell death of mesenchymal stromal cells (MSCs) in vitro. Gas chromatography–mass spectroscopy confirmed the spectrum of active components in the extract. Out of the three different extracts, the hexane extract showed significant free radical scavenging activity. Treatment of MSCs with H2O2 (hydrogen peroxide) significantly increased intracellular cell death; however, pretreatment with TS extract and nanoparticle-loaded TS (200 μg/ml) suppressed H2O2-induced elevation of Cyt-c and MMP13 and increased the survival rates of MSCs. H2O2-induced (0.1 mM) changes in cytokines were attenuated in the extract and nanoparticles by pretreatment and cotreatment at two time points (p<0.05). H2O2 increased cell apoptosis. In contrast, treatment with nanoparticle-loaded TS suppressed the percentage of apoptosis considerably (p<0.05). Therefore, TS may be considered as a potential candidate for enhancing the effectiveness of MSC transplantation in cell therapy.